Globalization of R&D and China: Empirical Observations and Policy Implications - Nannan Lundin; Sylvia Schwaag Serger (Research Institute of Industrial Economics (IFN), 2007)
As one of the worlds largest recipients of Foreign Direct Investment (FDI), China is emerging as a key global player in Research and Development (R&D). This rapid increase in R&D investment is mainly attributed to the effort of strengthening the indigenous innovation capacity of domestic actors and, to an increasing extent, to the process of globalization of R&D with multinational enterprises as key driving force. This paper provides a detailed overview of the relative importance of foreign R&D in China based on quantitative mapping in terms of R&D inputs, outputs and local linkages in R&D-related activities, combined with an in-depth description of the nature of foreign R&D activities. Our empirical observation suggests that the growing importance of China in the globalization of R&D is more than a flash-in-the-pan. On one hand, China is facing new challenges, but at the same time is attempting to seize the window of opportunity to compete for knowledge and human resources through structural adjustments and new policy initiatives. On the other hand, multinational enterprises from OECD countries are not only intensifying, but also diversifying their activities in a larger number of R&D intensive sectors in China. In such a rapid and dynamic development, China seems to emerge not only as an important source of R&D but also a key magnet of global R&D operations.
Keywords: F23; O31; O32; 330; China; R&D; Globalization; Multinationals; Multinationales Unternehmen; Betriebliche Forschung; Globalisierung; China